Artificial Surface-Induced Inflammation Relies on Complement Factor 5: Proof From a Deficient Person - Bergseth, Grethe; Lambris, John D.; Mollnes, Tom Eirik; Lappegård, Knut Tore (The Annals of thoracic surgery, 2011)
Exposing blood to artificial surfaces results in an inflammatory response, including complement activation and cytokine release. The aim of this investigation was to study complement-dependency and independency in artificial surface-induced inflammation in human whole blood from a patient with a genetic deficiency of complement factor 5 (C5). Whole blood from a C5-deficient patient, C5 protein reconstituted blood, and blood from a control subject was used. The complement inhibitor compstatin (C3 inhibitor) and a C5a receptor antagonist were used to block complement. Blood was circulated in closed loops of polyvinyl chloride tubing. Leukocyte CD11b expression and release of granule enzymes (myeloperoxidase, elastase, lactoferrin), cytokines (interleukins, chemokines, and growth factors; n = 27) as well as complement activation were measured after incubation. In C5-deficient blood, there was no formation of the terminal complement complex, as opposed to reconstituted or control blood. Release of granule enzymes was partly dependent on C3, revealed by a compstatin-dependent effect in C5-deficient blood, and partly C5a-dependent as evident from the reconstitution and control blood. The chemokines interleukin-8 and monocyte chemoattractant protein-1 were also highly complement dependent, the effect being C5a-mediated, whereas platelet-derived and vascular endothelial growth factors were partly complement dependent. Interferon-γ increased in a complement-independent manner, whereas the rest of the cytokines did not respond to the surface. Leukocyte expression of CD11b was only marginally increased in deficient blood exposed to the surface, whereas reconstitution induced a considerable, C5a-dependent increase, comparable with that of the control. The polyvinyl chloride surface induced a defined inflammatory response, which largely depended on C5.